REALITAS TROTOAR DALAM NEW MEDIA ART - Heru Firdaus, Dra. Jupriani, M.Sn., Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2018)
This final project aimed to remind people, government, including myself to use the sidewalk as it should be. Due to the misuse of sidewalk, a lot of bad things happened. Besides, this project employed 5 steps which were Preparation, Elaboration, Synthesis, Concept realization, and Completion. The artworks displayed were about the realities that often happened, and some of the were about the misuse of sidewalk. These artworks included Lupa, Roda Trotoar, Berjalan di Udara, Penghuni Trotoar, Jejak, Taman Kota, Save Stand, Toy, Step in to the hole, and Troto-War.Keywords : Reality, Sidewalk, New media Art